PERSEPSI TAREKAT KHALWATIYAH YUSUFIYAH TENTANG AYAT-AYAT ZIKIR (SUATU KAJIAN LIVING QUR’AN) - Faried, Muhammad Nawir; Abubakar, Achmad; Damis, Rahmi (Aqidah-Ta: Jurnal Ilmu Aqidah, 2022)
The main problem of this research is the understanding of the Khalwatiyah Yusufiyah Congregation about the verses of the Qur’an which are used as the basis for remembrance of Allah swt., the implementation and effects of its practice. The type of research is a field research which is qualitative-descriptive. The approaches used are interpretation, socio-historical, and Sufistic. The source of the data for this research is the sheikh or murshid of the Khalwatiyah Yusufiyah Order, the caliph and his followers. The data collection methods are observation, interviews, and documentation. Then the data processing and analysis techniques were carried out through three stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the interpretation of the Qur’anic verses about remembrance by the Khalwatiyah Yusufiyah Order which is used as the basis for remembrance (for example, QS al-Ahzab/33:41-42) has differences with the commentators of the pronunciation of z ikran kası>ra> (remembrance as much as possible). Meanwhile, QS al-Syu>ra/42:11 and QS al-Baqarah followers of the Yusufiyah Khalwatiyah Order are the same as those expressed by the commentators. The practice of followers of the Khalwatiyah Yusufiyah Order is to do remembrance every time, every time, and every day. After the fardu prayer, dhikr, praying jahar or sir, especially on Friday nights based on the direction of the Murshid, the effect makes them pray diligently, their faith increases, their behavior is good, solidarity with fellow humans is good, their social spirit is high. The implication is, hopefully it can provide insight into remembrance for everyone, especially the congregation of the Khalwatiyah Yusufiyah congregation. And to the Murshid and or the caliph to give (add) lessons regarding the understanding of the verses of the Qur’an about remembrance